A Right Gastroepiploic Artery Aneurysm Treated by Surgical Excision - Hyangkyoung Kim; Yong-Pil Cho; Ki-Myung Moon; Sang-Joon Park; Tae-Won Kwon (Annals of surgical treatment and research, 2010)
A 65-year-old male patient was referred to our hospital for postprandial abdominal pain. Computed tomography and angiography revealed 2 aneurysms of the right gastroepiploic artery, which were measured 0.8×1.3 cm and 1.9×3.4 cm. Excision of 2 saccular and fusiform aneurysms by laparotomy was performed. His hospital course was uneventful and symptoms disappeared after surgery. A gastroepiploic artery aneurysm can cause recurrent abdominal pain and surgical resection is warranted in symptomatic aneurysms. KCI Citation Count: 1